SOPHISTICATION IN THE USE OF BUDGETING PRACTICES - Suave, Ricardo; Lunkes, Rogério João; Petri, Sérgio Murilo; Rosa, Fabricia Silva da (Advances in Scientific and Applied Accounting, 2016)
Previous studies regarding the budgeting practices topic seek to conduct surveys about what budgeting practices are used by companies, but there is no initiative to indicate which of them can be best suited. This paper aims to construct a model to assess the level of sophistication of the budgeting practices of companies. To build the model, we used MCDA-C (Multicriteria Decision Aiding - Constructivist) methodology. We developed the model with the use of a value function for conversion of the scale, the method of the Direct Score was used. The model enables the demonstration of the sophistication level in the use of surveyed budgeting practices as well as for comparisons between research in different countries and industries. Using an instrument from another area of knowledge, the model contributes to measure the sophistication level of budgeting practices used.